Predictors of green purchase intention toward eco-innovation and green products: Evidence from Taiwan. Issue 2 (10th July 2023) - Moslehpour, Massoud; Chau, Ka Yin; Du, Lijie; Qiu, Ranfeng; Lin, Chia-Yang; Batbayar, Batzaya
Abstract: Recently, purchasing intention towards green products has gained global attention due to their extensive use and high environmental issues. Thus, the current article investigates environmental concern, environmental knowledge, green product, and eco-innovation influence on the green purchase intention of green products in Taiwan industry. The research also examines the mediating role of consumers' attention among environmental concerns environmental knowledge, green products eco-innovation, and green purchase intention. The article used questionnaires to collect the primary data from the sampled population. To examine the hypothesis, the PLS methodology was adopted. The results indicated that environmental concern, environmental knowledge, green product, and eco-innovation have a positive association with green purchase intention. The findings also exposed that consumer attention significantly and positively mediates environmental concern, environmental knowledge, green product, eco-innovation, and green purchase intention. The paper also proposed some guidelines to the practitioners which help them in the development of green-related policies to increase purchase intention.